¿Niños delincuentes? fundamento de su punibilidad en el derecho penal moderno. - Castro Ortiz, Medardo German (2014)
Crime is a characteristic phenomenon of all the economic and social formations through which humanity passes, one of its manifestations at present is juvenile delinquency, which even when it is harmful; Because it is a process that fundamentally has its radius of action in the territorial frameworks, Criminal Law has not been able to confront it because it falls outside its competency frameworks, as we will analyze in detail in the development of the investigation. That is why the motivations arise to deepen the paths of juvenile delinquency and its treatment from the point of view of Criminal Law, taking into account that the investigative background of the subject in the province, is the Diploma Work: “Minority of age and Straight. Critical analysis of its incidence in Latin America ”, where the situation of juvenile delinquency and its incidence in Latin America was developed from a criminological point of view.